2017
DOI: 10.21928/juhd.v3n1y2017.pp288-296
|View full text |Cite
|
Sign up to set email alerts
|

Design a Mobile Learning Framework for students in Higher Education

Abstract: ML (mobile learning) has extended e-learning to a new paradigm of “anywhere, anytime learning”. The use of 3G and 4G Phones (high-speed data transfer) will be represented as a great opportunity for both learners and teachers to meet together, access and exchange information in virtual spaces whilst on the move. The aim of this work is to design a mobile learning framework for Students in higher education. Thus, this will provide better quality of teaching. Additionally, Mobile learning (M-learning) has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Blended learning has turned out to be prominent among the most known approaches to educate English as Foreign Language (EFL). In [41], the authors outline M-learning framework based on three key aspects: technical, cultural and theoretical aspects. The validation of the framework is conducted by questionnaires with students but there is a lack of clarity on the validation process and applied areas of learning.…”
Section: Frameworkmentioning
confidence: 99%
“…Blended learning has turned out to be prominent among the most known approaches to educate English as Foreign Language (EFL). In [41], the authors outline M-learning framework based on three key aspects: technical, cultural and theoretical aspects. The validation of the framework is conducted by questionnaires with students but there is a lack of clarity on the validation process and applied areas of learning.…”
Section: Frameworkmentioning
confidence: 99%
“…With the increased usage of mobile phones, the government has made it easier for institutions to engage in design and developing m-learning applications by facilitating the development of ICT tools for teaching and learning [15]. Higher education institutions have increasingly used web pages and Internet resources with essential learning materials and online learning (e-learning) still visually impaired students cannot benefit fully on accessibility [1]. According to [16], there are an estimated five HLI in Tanzania who uses m-leaning integrated into Moodle learning management system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[20]discussed incorporation clouding computing on mmlearning for commerce, healthcare, and educations system to improve productivity in the nation. However [1] designed a framework for m-learning to be used in Higher institutions which motivate students to use it and learn in order to increase mobility and efficiency. [21]designed m-learning for professional development of the people especially those who are in offices who are not visual impaired [23]found that it is advantageous to use cloud computing for e-learning solutions and it influences the way the e-learning software projects are managed.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile applications tend to bring valuable results to learning in challenging learning environments [3] [4]. Farrah's research shows that most students use mobile applications because of the ease of accessibility and flexibility that helps them in the teaching and learning process.…”
Section: A Mobile Application For Learningmentioning
confidence: 99%